Implementation Of A Profile Matching Based Decision Support System For Selecting Eligible Candidates Of Kip College Scholarships At Sam Ratulangi University - Hierro Deandro Frederik Dannari; Benny Pinontoan; Mahardika I. Takaendenga (International Journal of Health Engineering and Technology, 2026)
The implementation of the KIP Kuliah scholarship program at Sam Ratulangi University (UNSRAT) faces challenges in ensuring objective, transparent, and accurate recipient selection due to limitations in the verification process. This study aims to develop and implement a web-based Decision Support System (DSS) using the Profile Matching method to support the selection of eligible KIP Kuliah scholarship recipients. The system was developed using the Waterfall methodology, including requirements analysis, system design, implementation, testing, and deployment, and was implemented using PHP, MySQL, and HTML/CSS. The evaluation employed six assessment criteria consisting of three Core Factors (parental income, family asset ownership, and number of family dependents) weighted at 60% and three Secondary Factors (academic performance, parents' employment status, and living condition) weighted at 40%. The Profile Matching algorithm calculates the GAP between applicant profiles and the ideal profile to generate recommendation rankings. Functional evaluation using Black-box Testing confirmed that all system modules operated according to their specifications. Validation using simulated applicant data demonstrated that the proposed system generated objective and consistent recommendation results based on the predefined criteria. The developed DSS improves the efficiency, transparency, and objectivity of the KIP Kuliah scholarship selection process at Sam Ratulangi University.